Hubungan Peralihan Fungsi Lahan Terhadap Penerapan Peraturan Perpajakan - Ahmad Nashih Mustofa; Frans Vernando Marlius Pardede; Muhammad Senopati Willmar Siladja Putra; Pupus Ardhi (Publikasi Indonesia, 2021)
This study aims to determine the relationship between land use change and taxation. This research uses a qualitative approach. The method used is documentative study. After the data was collected, reduction was carried out according to the research keywords. After that, data processing and writing are carried out in the form of scientific papers. In Law 28/2009, the central government transfers rural and urban land and building taxes to local governments. This affects the land transfer tax and in the legislation it is stated that it is classified as land and building tax. However, land and building taxes originating from land covering the three mining, forestry and plantation sectors are still collected by the central government. Land and building tax devolution aims to increase regional government revenue autonomy, increase regional revenues, and reduce local government dependence on fiscal transfers from the central government. To increase autonomy, the central government not only delegates responsibility for administering land and building taxes, but also gives certain powers to local governments to make policies. However, mining and forestry in particular is a very politically sensitive sector, which is one of the main reasons why decentralization of property taxes for plantations seems more likely in the near future than for mining and forestry.